ANALISIS KIMIA BEBERAPA JENIS KAYU DARI INDONESIA BAGIAN TIMUR (Chemical analysis of several wood species from East Indonesia) - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1996)
This paper  reported  the  result  of  chemical  analysis  of  nine  wood  species  from  East Indonesia.  The analysis comprise of the determination  of  holocellulose,  cellulose,  lignin,  pentosan,  ash  content,  silica  content  and the solubility  in cold water,  hot water,  one percent  of  sodium  hydroxide and alcohol  benzene extractives.  These analysis  were conducted to determine their basic characteristics and ultimate uses of the wood. The result showed that holocellulose  content ranges from  66,91 - 75,29 %, cellulose from  43,50- 54,72 %, lignin from  24,04 - 33,09  %, pentosanfrom   14,34 - 18,95  %, ash content from  0,38  - 2,13  %, silica content from  0,12 -1,91  %, The solubility in cold water rangesfrom 2, 71  -  8,42  %, hot water from  2,87 - 8,92  %,  in NaOH 1  % from  12,34  - 26,65   %  and in alcohol benzena (1:2) from  2,42-11,86  %. Based on chemical analysis,  especially  the  cellulose content the 9 wood species from  East Indonesian are suitable as raw material for pulp and paper industry.Keywords:   IBT, Chemical Component.